Delivering on the Promise of Democracy Visual Case Studies in Educational Equity and Transformation - Jhaj, Sukhwant (Open Reports Series, 2019)
"Many educators can recite the faults of their schools or universities, but far fewer can recognize and develop existing strengths to benefit a wider audience. Sukhwant Jhaj has crafted a refreshing new look at how imaginative leadership and a shift in perspective can propel institutions to reach at-risk or underrepresented members of their communities. Delivering on the Promise of Democracy pulls back the curtain on seven high-performing universities to reveal which daily decisions, including listening to the community, embracing conflict, and implementing effective strategies through routine, guide administrators in achieving exceptional results. Through in-depth interviews that offer a close look at these seven universities, Jhaj traces a new trajectory for higher education: a call to question a university's effectiveness through its accessibility to the community it serves. Jhaj's book will inspire anybody interested in widening access to education with its call to renew their institution's mission through powerful and effective leadership. "